The effects of epidural analgesia in normal labour - Reddy, Vallur Swetha; Sabitha, U. S.; Krishna, L.; ., Vimala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Epidural analgesia is considered to be gold standard technique for labour analgesia but is claimed to prolong labour. Previous studies have evaluated epidural analgesia versus systemic opioids to no analgesia. The present study evaluated the effect of epidural analgesia on duration of labour compared to no analgesia. Methods: Sixty primigravida with full term-singleton, vertex presentation in spontaneous labour were included in the study. Parturient willing for epidural analgesia were allocated as epidural group (n=30), rest served as control. The intervention in active stage of labour included 10 ml of Inj. Bupivacaine 0.125% and Inj. Fentanyl 100μg and maintenance with infusion of Inj. Bupivacaine 0.125% and Inj. Fentanyl 2μg/ml added at a rate of 6-8 ml/hr. Duration of the first two stages of labour, patient satisfaction, side effects, number of instrumental vaginal/ vacuum-assisted deliveries, and neonatal APGAR score were recorded. Results: The mean duration of first stage of labour was shorter in epidural group (250.17±106.33 minutes) compared with control (302.00±111.99 minutes), (p= 0.071). The mean duration of second stage in epidural group was (18.73±6.82 minutes) compared with control (18.33±14.53 minutes) was not significant (p= 0.892). Although instrumental vaginal delivery rate was greater in the epidural group (6.7%) as compared to control (3.3%), (p=1.000). Pain score (VAPS) varied between1-3 and 4-10 in epidural group and control respectively (p< 0.001). The APGAR scores at 5 min and neonatal ICU admissions were statistically comparable. Conclusions: Epidural analgesia with Bupivacaine and Fentanyl results in good pain relief with undue prolongation of labour.